2019
DOI: 10.1186/s12870-019-1948-y
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The specific MYB binding sites bound by TaMYB in the GAPCp2/3 promoters are involved in the drought stress response in wheat

Abstract: Background Drought stress is one of the major abiotic stresses that affects plant growth and productivity. The GAPCp genes play important roles in drought stress tolerance in multiple species. The aim of this experiment was to identify the core cis-regulatory elements that may respond to drought stress in the GAPCp2 and GAPCp3 promoter sequences. Results In this study, the promoters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…It has been shown that cis-acting elements in the promoter region are closely related to gene function (Chow et al, 2018). Consistent with their expression profiles, GmDUF4228 genes contained a variety of cisacting elements related to abiotic stresses, including MYB, MYC, MBS, and GT-1 elements (Figure 6), which play an important role in response to drought and salt treatments (Abe et al, 1997;Li et al, 2018;Tang et al, 2019;Zhang L. et al, 2019). Studies have shown that MYC also functions in cold stress (Ohta et al, 2018) and disease resistance (Lorenzo et al, 2004).…”
Section: Discussionmentioning
confidence: 65%
“…It has been shown that cis-acting elements in the promoter region are closely related to gene function (Chow et al, 2018). Consistent with their expression profiles, GmDUF4228 genes contained a variety of cisacting elements related to abiotic stresses, including MYB, MYC, MBS, and GT-1 elements (Figure 6), which play an important role in response to drought and salt treatments (Abe et al, 1997;Li et al, 2018;Tang et al, 2019;Zhang L. et al, 2019). Studies have shown that MYC also functions in cold stress (Ohta et al, 2018) and disease resistance (Lorenzo et al, 2004).…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies indicate that MYB proteins participate in wheat response to environmental stress. For instance, TaMYB can bind to the specific MYB binding sites in the promoter fragments to upregulate the expression levels of GAPCp2 and GAPCp3, which are involved in drought stress response in wheat [20]. Overexpression of TaMYBsm3-D increases the drought tolerance of transgenic Arabidopsis through upregulating P5CS1, DREB2A, and RD29A [21].…”
Section: Introductionmentioning
confidence: 99%
“…The results ( Fig. 5 ) showed that MYB, MBS, TC-rich, LTR, GT1-motif, G-Box, GA-motif, W-Box, ABRE, ERE, and GARE-motifs, which were related to drought tolerance ( Zhang et al, 2019 ), flavonoid biosynthesis ( Wang et al, 2018 ), defense and stress responsiveness ( Zhang et al, 2005 ), low temperature tolerance ( Feng et al, 2019 ), light response ( Zhang et al, 2013 ; Zhu et al, 2015 ), abiotic stress responsiveness ( Yan et al, 2019 ), abscisic acid responsiveness ( Choi et al, 2005 ), ethylene responsiveness ( Rawat et al, 2005 ), and gibberellin responsiveness, were found in promoters of the 26 BpDof genes. Among these, MYB, MBS, G-Box, GT1-motif, ABRE, and ERE cis-elements were abundant, thus suggesting that these BpDof genes might be involved in drought tolerance, light response, and ABA- and ethylene-responsive signaling.…”
Section: Discussionmentioning
confidence: 99%